(untitled) (Conferencea, 2023)
Junior school age ranges from 6-7 to 11 years old ( I - IV classes). Peculiarities of age-related development. Junior school age is characterized by a uniform development of the locomotor apparatus, but the intensity of growth varies in its specific proportions.